Teaching Crime Fiction (Teaching the New English, 2018)
More than perhaps any other genre, crime fiction invites debate over the role of popular fiction in English studies. This book offers lively original essays on teaching crime fiction written by experienced British and international scholar teachers, providing vital insight into this diverse genre through a series of compelling subjects. Taking its starting-point in pedagogical reflections and classroom experiences, the book explores methods for teaching students to develop their own critical perspectives as crime fiction critics, the impact of feminism, postcolonialism, and ecocriticism on crime fiction, crime fiction and film, the crime short story, postgraduate perspectives, and more.